Pengaruh Moralitas, Kompensasi, Kompentensi dan Sistem Pengendalian Internal Terhadap Kecurangan Pengelolaan APBDes : (Studi di Kecamatan Lubuk Batu Jaya, Kabupaten Indragiri Hulu) - Sidabutar, Monica Enjelina; Azhari, Intan Putri; Suriyanti, Linda Hetri (Yayasan Jompa Research and Development, 2024)
The rise of corruption cases in Indonesia should be immediately prevented to prevent fraud from the management of the APBDes so that the funds that have been distributed can be useful for building. Various factors cause the fraud, such as morality, compensation, competence and internal control system in the management of the APBDes.In this study will be tested the relationship of each variable with apbdes management fraud in Lubuk Batu Jaya district. This study uses quantitative research methods with primary data types. Techniques in collecting data using questionnaires that will be given to respondents totaling 63 taxpayers as a sample of 180 population. This study used purposive sampling technique .To test the researchers used multiple linear regression method. The results of this study showed that that morality(X1) showed that the count (-0.421) <ttable (2.001) and the significance level of 0.675 > 0.05, it can be concluded that the morality variable (X1) against cheating (Y) or the first hypothesis (H1) was rejected. compensation(X2) shows that the count (3.377) >ttable (2.001) and the significance level of 0.001 < 0.05, it can be concluded that the compensation variable (X2) against fraud (Y) or the second hypothesis (H2) is accepted. competence(X3) shows that the count (0.057) < ttable (2.001) and the significance level of 0.955 > 0.05, it can be concluded that the competence variable (X3) against fraud (Y) or the third hypothesis (H3) rejected. Internal control(X4) shows that the count (-0.670) <ttable (2.001) and the significance level of 0.505 > 0.05, it can be concluded that the variable of Internal Control (X4) against fraud (Y) or the fourth hypothesis (H4) is rejected.0,060>0,05.